2004
DOI: 10.1177/1097184x03260958
|View full text |Cite
|
Sign up to set email alerts
|

“It’s Different for Men”

Abstract: Drawing on interview data with men and women who have engaged with in vitro fertilization (IVF) unsuccessfully, this article explores the ways in which men experience and make sense of the failure of treatment. Focusing on men's experiences of infertility, their perceptions of IVF as a technology, and their involvement in the IVF process, the analysis highlights the ambivalent relationship between men and IVF as a technology; the predominance of hegemonic masculine culture in mediating the meaning of IVF for b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
82
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(89 citation statements)
references
References 14 publications
4
82
0
3
Order By: Relevance
“…Men in our study mainly used the Internet or talked to their partners to get knowledge and support, and said that discussions with others felt like prying. This is in line with a study by Throsby and Gill (2004) where men did not feel they got supportive responses from within the male community. A study by Peronace, Boivin, and Schmidt (2007) also showed that even positive support from the men's social networks was reduced or changed negatively over time.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Men in our study mainly used the Internet or talked to their partners to get knowledge and support, and said that discussions with others felt like prying. This is in line with a study by Throsby and Gill (2004) where men did not feel they got supportive responses from within the male community. A study by Peronace, Boivin, and Schmidt (2007) also showed that even positive support from the men's social networks was reduced or changed negatively over time.…”
Section: Discussionsupporting
confidence: 92%
“…This delayed the decision to get help. Other studies have found similar reluctance to make the decision to seek help, both for women White et al, 2006) and men (Throsby & Gill, 2004).…”
Section: Discussionmentioning
confidence: 88%
“…In other cases, women praised and protected their husbands, clearly committed to the conjugal relationship and choosing not to reveal the cause of infertility because "it would be degrading to your husband." Walle (2004) has written about the way in which maintaining secrecy around things which might cause shame provides protection for Pakistani men; families comply with this as it is in their interest as well, but this extends beyond Pakistani men, including to white British men (see Throsby and Gill 2004).…”
Section: Conjugality Blame and Disengagementmentioning
confidence: 99%
“…Participants were interviewed individually. Previous research suggests that individual interviews allow participants, particularly men, to express negative perspectives or distress that they may wish to conceal from their partner (Glover et al, 2009;Throsby and Gill, 2004). The interview schedule drew on the selfregulatory, stress, coping and infertility literature.…”
Section: Data Collectionmentioning
confidence: 99%